1968
DOI: 10.1172/jci105780
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial mechanics in aortic and mitral valvular regurgitation: the concept of instantaneous impedance as a determinant of the performance of the intact heart

Abstract: A B STR A C T The effects on myocardial mechanics of acute, artificial aortic and mitral regurgitation were studied in the dog to determine the manner in which the changes in load induced by valvular regurgitation alter ventricular performance. With mitral and aortic regurgitant volumes of approximately the same magnitude as the forward stroke volume, immediate increases occurred in total stroke volume, left ventricular enddiastolic pressure, and peak ejection velocity, whereas contractility remained unchanged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1
2

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(38 citation statements)
references
References 27 publications
0
35
1
2
Order By: Relevance
“…However, the LVSs and LVDs, and EFs so obtained were presumably satisfactory for intergroup comparisons. Although never reaching statistical significance, the MR group tended to have slightly greater ventricular motion compared with the no MR group, perhaps reflecting the unloading effect of MR. 37 The conclusion drawn from this study contrasts with that from a previous autopsy study. 4 Postmortem changes conceivably may occur, but echocardiographic and autopsy measurements of the mitral annular circumference in normal patients are similar.…”
Section: Methodscontrasting
confidence: 99%
“…However, the LVSs and LVDs, and EFs so obtained were presumably satisfactory for intergroup comparisons. Although never reaching statistical significance, the MR group tended to have slightly greater ventricular motion compared with the no MR group, perhaps reflecting the unloading effect of MR. 37 The conclusion drawn from this study contrasts with that from a previous autopsy study. 4 Postmortem changes conceivably may occur, but echocardiographic and autopsy measurements of the mitral annular circumference in normal patients are similar.…”
Section: Methodscontrasting
confidence: 99%
“…In this study neither peak dP/dt nor peak dP/dt normalized to end-diastolic volume changed upon ductal occlusion (33). Thus, it appears that the LV was unable to augment contractility as expected in the presence of the left-to-right shunt and increasing volume load (31). It has been demonstrated that sympathetic innervation of the heart is incomplete at term and the ncwborn LV may be more dependent on and sensitive to circulating catecholamines (14,34).…”
Section: Discussionmentioning
confidence: 50%
“…(1) The potential beneficial impact of valve repair on survival is controversial26'49 and has been analyzed separately.61 (2) The current study demonstrates that left ventricular dysfunction is associated with excess late mortality even in patients who have a valve repair. (3) Preoperative variables remained independent predictors of survival in a combined model incorporating the type of correction performed.…”
Section: Discussionmentioning
confidence: 91%